ไฮโดรจิเนชันของคาร์บอนไดออกไซด์เป็นโอเลฟินส์เบาบนตัวเร่งปฏิกิริยาเส้นใย Co-Fe/CNT-SiO2 - กนกกร พงษ์ภมร (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Dealing with carbon dioxide waste is an on-going societal and technological challenge. One attractive proposition is to chemically convert waste carbon dioxide into useful chemical products. One possible route is to combine two well-known chemical processes, reverse water gas shift and Fischer-Tropsch synthesis, to make a catalyst capable of converting carbon dioxide directly into hydrocarbons. Catalytic hydrogenation of CO2 to hydrocarbons is a modification of Fischer-Tropsch synthesis (FTS), where CO2 is used as reactant instead of CO. My research deals with the development of active, selective and stable catalysts based on cobalt-iron with carbon nanotube-silica fiber (CNT-SiO2 fiber) as support (10CoFe/CNT-SiO2 fiber). One of the major focuses is the surface modification of CNTs to the catalytic performance of cobalt-iron catalysts in CO2 hydrogenation. And to promote with potassium ion exhibited the higher olefins product (10CoFe-K/CNT-SiO2 fiber). The modification by potassium metal ion can decrease the hydrogenation ability (suppress methane product) and increase the chain-growth probability. So that, the best condition of CO2 hydrogenation to produce olefins of reaction were 350°C, 25 bar, W/F 10 g(cat)•h/mol. Using 10CoFe-10K/CNT-SiO2 fiber can produce highest olefins product and suppress the methane formation. With %CO2 conversion = 40.90, %Selectivity of C2-C4 olefins = 8.79